Identification of Mineralocorticoid Receptors, Aldosterone, and Its Processing Enzyme CYP11B2 on Parasympathetic and Sympathetic Neurons in Rat Intracardiac Ganglia - Dehe, Lukas; Mousa, Shaaban A.; Aboryag, Noureddin; Shaqura, Mohammed; Beyer, Antje; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Neuroanatomy, 2022)
Recent interest has focused on the mineralocorticoid receptor (MR) on heart performance. Apart from its known expression in the myocardium, there is a lack of evidence for an expression of MR and its endogenous ligand aldosterone in neurons of the intrinsic cardiac nervous system. Therefore, we looked for evidence of MR and its endogenous ligand aldosterone in sympathetic and parasympathetic neurons of atrial intracardiac ganglia. Tissue samples from rat heart atria were subjected to conventional reverse-transcriptase polymerase chain reaction (PCR), Western blot, and double immunofluorescence confocal analysis of MR, corticosterone-inactivating enzyme 11ß-Hydroxysteroid-Dehydrogenase-2 (11β-HSD2), aldosterone and its processing enzyme CYP11B2 together with the neuronal markers vesicular acetylcholine transporter (VAChT) and tyrosine hydroxylase (TH). Our results demonstrated MR, 11β-HSD2 and CYP11B2 specific mRNA and protein bands in rat heart atria. Double immunofluorescence confocal microscopy revealed co-expression of MR immunoreactivity with VAChT in large diameter parasympathetic principal neurons. In addition, MR immunoreactivity was identified in TH-immunoreactive small intensely fluorescent (SIF) cells and in nearby VAChT- and TH-immunoreactive nerve terminals. Interestingly, the endogenous ligand aldosterone and its synthesizing enzyme CYP11B2 as well as 11β-HSD2 co-localized in MR-IR neurons of intracardiac ganglia. Overall, this study provides firm evidence for the existence of not only local expression of MR but also of 11β-HSD2 and endogenous ligand aldosterone with its processing enzyme CYP11B2 in the cardiac autonomic nervous system suggesting a modulatory role of the mineralocorticoid system on the endogenous sympathetic and parasympathetic neuronal activity on heart performance.